Mineral binders and concretes based on technogenic waste - Haqverdieva, Tahira; Akhmednabiev, Rasul; Bondar, Lyudmyla; Popovich, Nataliia (Academic journal Industrial Machine Building Civil Engineering, 2020)
Compositions of alkali-mineral binders based on wastes of alumina industry with application of research physicochemical methods have been developed. It has been established that impregnations with hot CaCl2 solution accelerate the curing time. It has been established that the conditions of hardening significantly influence the physical-mechanical properties. The developed binding materials with a compressive strength of 40.0… 65.1 MPa belongs to hydration-condensation, alkaline-alkaline type. The results of studies on the ash slag influence from circulating fluidized bed boilers on the heavy concrete properties are presented. The studies were carried out using mathematical planning of the experiment. Mechanical concrete properties have been studied using in the study of freeze-thaw resistance, the dilatometry method was applied.
Keywords: alkali-mineral binders; compressive strength; DTA-analyses; fine-grained concretes; industry wastes; IR- spectrum; slags of TPP; X -ray analysis